The Effectiveness of Using the Kahoot Application in Developing the Ability to Understand Mathematical Concepts of Junior High School Students - Nida Sri Utami; Suci Ati Qomariyah (Eduvest - Journal of Universal Studies, 2025)
This study examines the effectiveness of Kahoot!, a game-based learning platform, in improving junior high school students’ conceptual understanding in mathematics. A quasi-experimental method was applied involving two eighth-grade classes at SMP Negeri 2 Teras: one as the experimental group using Kahoot and the other as the control group receiving conventional instruction. Data were gathered through pretests, posttests, questionnaires, and observations. The t-test analysis revealed a significant difference in student performance (t_count = 2,4132 > t_table = 2.0086 at α = 0.05), with the experimental group achieving a moderate N-Gain of 0.56. These findings demonstrate that Kahoot fosters student engagement, encourages real-time feedback, and supports varied learning styles, contributing to enhanced conceptual understanding. The integration of Kahoot in mathematics instruction, particularly on abstract topics like statistics, is shown to create a more interactive and student-centered learning environment. Educators are encouraged to incorporate technology-enhanced tools such as Kahoot to support active and meaningful learning processes.